Hiperhomosisteinemia dan Faktor Risiko Kelainan Vaskuler - Gugun, Adang Muhammad (Fakultas Kedokteran dan Ilmu Kesehatan Universitas Muhammadiyah Yogyakarta, 2008)
Homocysteine is a sulfhydryl-containing amino acid derived from the essential amino acid methionine, which is abundant in animal sources of protein. Raised plasma homocysteine (tHcY) concentrations are caused by genetic mutations, vitamin dificiencies, renal and ather diseases, numerous drugs and increasing age. Raised tHcY concentrations are associated with laboratory evidence of atherothrombotic. In experimental studies, homocysteine causes oxidative stress, damages endothelium, and enhances thrombogenicity. Epidemiological studies have shown that too much homocysteine in the blood (plasma) is related to a higher risk of coronary heart disease, stroke and peripheral vascular disease. Supplementation of folic acid with vitamin B6 and Bn combination can be lowering homocysteine. There is currently insufficient evidence to recommend routine screening and treatment of high tHcy concentrations with folic acid and other vitamins to prevent atherothrombotic vascular disease. There is the discordance between the epidemiology of homocysteine and the results of the clinical trials.Homosistein adalah asam amino sulfhydril, merupakan senyawa antara yang terbentuk dalam metabolisme asam amino esensial metionin, banyak berasal dari protein hewani. Peningkatan homosistein disebabkan oleh mutasi genetik, defisiensi vitamin, penyakit ginjal dan penyakit lain, obat-obatan dan peningkatan usia. Peningkatan kadar homosistein menyebabkan aterotrombosis. Homosistein menyebakan stress oksidatif, kerusakan endotel (disfungsi endotel) dan memacu trombosis. Studiepidemiologimemperlihatkan peningkatan homosistein plasma beihubungan dengan kejadian penyakit jantung koroner, stroke dan penyakit pembuluh darah perifer. Pemberian suplemen asam folat dengan kombinasi vitamin B6 danvitaminB12 menurunkan kadar homosistein. Buktiyang kuat untuk memberikan asam folat atau vitamin lainnya secara rutin maupun dalam terapi untuk pencegahan penyakit aterotrombosis belum didapatkan. Terdapat ketidaksesuaian antara studi epidemiologi dan clinical trial.